2014
DOI: 10.1111/cid.12288
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow‐Up of Dental Implants Placed in Autologous Onlay Bone Graft

Abstract: We suggest that augmentation of severely atrophied jaw bone through the placement of horizontal and/or vertical intraoral OBGs in combination with Bio-Oss saturated with PRP and covered by PPP should be considered a reliable, safe, and very effective surgical technique for obtaining high bone graft survival rate and high long-term implant survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
2
26
1
Order By: Relevance
“…Two studies added Bio‐Oss to the AB block, and one study added particulate beta‐tricalcium phosphate . One study used only Bio‐Oss blocks, and finally one study used AB block with particulate Bio‐Oss and platelet‐rich plasma . The most common harvest site was the iliac crest, which was used in nine studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies added Bio‐Oss to the AB block, and one study added particulate beta‐tricalcium phosphate . One study used only Bio‐Oss blocks, and finally one study used AB block with particulate Bio‐Oss and platelet‐rich plasma . The most common harvest site was the iliac crest, which was used in nine studies.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in the data presented in Table , a clear trend was the evaluation of implant survival solely, rather than overall success, when defining the success criteria. Thus, 12 studies cited implant survival as their main outcome, while five studies stated that they intended to use some predefined criteria for success assessment (eg, Albrektsson et al, Buser et al), although this goal was not necessarily achieved. Of those studies reporting a success rate, one study reported a survival rate and patients' subjective sensation, one study reported a survival rate, clinical parameters and patients' subjective sensation, and one study reported a survival rate and clinical parameters .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological long‐term data indicate that these nonautologous particles may often be well osseointegrated but that they sometimes may be surrounded by multinucleated giant cells, indicating a foreign body response in the tissue. Furthermore, long‐term follow‐up data in a recent study on implants placed in grafted sites indicated that even though a high survival rate was observed early after implant surgery, an increasing failure rates was observed in certain situations . Implant failure rates reaching 14‐35% after 5 years were reported in posterior jaws, indicating an ongoing inflammatory process at these grafted sites.…”
Section: Discussionmentioning
confidence: 99%